Bundle branch block and nonspecific intraventricular conduction delay prevalence using Chinese nationwide survey data. Issue 8 (August 2022) - Qiao, Qing; Lin, Jing; Chen, Ning; Xia, Shijun; Du, Jing; Du, Xin; Bai, Rong; Dong, Jianzeng; Ma, Changsheng
Objective: We aimed to determine the prevalence of and the factors associated with intraventricular conduction disturbance in the Chinese population. Methods: Electrocardiographic data from 42, 031 people were retrospectively analysed. The weighted prevalences of left bundle branch block (LBBB), right bundle branch block (RBBB), bifascicular block and nonspecific intraventricular conduction delay (NS-IVCD) were calculated. The independently associated factors were determined using logistic regression analysis. Results: The weighted prevalence for Chinese people older than 45 years was 0.17% for LBBB, 2.16% for RBBB and 0.44% for NS-IVCD. The weighted prevalence for RBBB combined with left anterior fascicular block was 0.17%, and 0.05% for RBBB combined with left posterior fascicular block. There were significant differences in the weighted prevalences of RBBB and NS-IVCD between men and women. The weighted prevalence of LBBB and RBBB increased markedly with increasing age. Age and diabetes were independent factors associated with LBBB, compared with age and sex for RBBB and sex and coronary artery disease for NS-IVCD. Conclusions: This study provided reliable data for the weighted prevalence of and factors associated with LBBB, RBBB and NS-IVCD in Chinese adults.